Effect of alcohol abuse on psycho-social well-being among young adolescents at Beere/Oja Oba Area, Ibadan, Oyo State, Nigeria (2021)
Alcoholic abuse has negative effect on young adolescents social and psychological well-being. The study examined the effect of alcohol abuse on psychosocial well-being of young adolescents who reside in Beere/Oja-Oba, Ibadan South East Local Government Area of Oyo State. The descriptive research design was used for the study while purposive sampling technique was employed to select one hundred and twenty (120) respondents. (Pearson product moment correlation, Multiple regression and chi-square were used to analyse the data. The findings revealed that there was no significant relationship between alcohol abuse/consumption and psychological wellbeing of young adolescents; there was no significant connection between alcohol abuse and social well-being among young adolescents; and that there was no significant consequence of alcohol abuse on interpersonal relationship of young adolescents. The study, therefore, recommended that key factors such as inculcating the idea of guidance counselor for young adolescents should make use of their time wisely and drink responsibly if they must drink and that any adolescent below eighteen years should not be allowed access to alcohol.